THE GEORGIAN POLITICAL ELITE: MAIN TRENDS OF ITS CIRCULATION - CHEDIA, Beka (CENTRAL ASIA AND THE CAUCASUS, 2015)
The author relies on the structure, nature, and values of the Georgian political elite to identify the ways and means through which it is replenished. He arranges the members according to their political clout, compares the central and regional elites, and examines the changing figures of the gender balance. The educational and professional levels, methods, and traditions of elite replenishment, as well as the conditions in which political careers develop serve as the starting point for assessing Georgia’s political context as lacking in political rivalry and stifled by prominent nepotism. The political elite and its interaction with the public elite are also discussed.